Testing the reflection of book value information and cash flows from operating activities on the market share price of banks listed on the Damascus Securities Exchange (Damascus University Journal for the economic and Political sciences, 2025)
This study aimed to test the relevance of the value of the book value of property rights information in comparison with the cash flows from the operating activities of the banks listed on the Damascus Stock Exchange. The study found, by relying on the secondary data published in the financial reports of banks listed on the Damascus Stock Exchange between 2012 and 2021 and by applying the modified Ohlson model, that the book value has an  relevance value, while the cash flows from operating activities do not have an relevance value.
Keywords: Stock Market Price; Value Relevance; Book Value; Cash Flows From Operating Activities